Advertisement Remove all ads

Solve the Following Equation: 4x2 + 4 Bx - (A2 - B2) = 0 - Mathematics

Sum

Solve the following equation: 4x2 + 4 bx - (a2 - b2) = 0

Advertisement Remove all ads

Solution

4x2 + 4 bx - (a2 - b2) = 0


`"x"^2 + "bx" - (("a"^2 - "b"^2))/4 = 0`


`"x"^2 + ("a + b")/2 xx -("a - b")/2 xx -("a"^2 - "b"^2)/4 = 0` 


`"x" {"x" + ("a + b")/2} - "(a - b)"/2 {"x" + ("a + b")/2} = 0`


`{"x" + (("a + b"))/2} {"x" - (("a - b"))/2} = 0`


`{"x" + (("a + b"))/2} = 0 , {"x" - (("a - b"))/2} = 0`


`"x" = -(("a + b"))/2 , "x" = (("a - b"))/2`

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

Frank ICSE Class 10 Mathematics Part 2
Chapter 6 Quadratic Equations
Exercise 6.1 | Q 16
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×